Safety of thoracic radiotherapy after PD‐(L)1 inhibitor treatment in patients with lung cancer - Yu Chen (Wiley, 2021)
Abstract Background The safety of thoracic radiotherapy (TRT) after programmed death 1/programmed death ligand 1 (PD‐(L)1) inhibitor treatment in patients with lung cancer was scarcely reported. This retrospective study was conducted to evaluate the incidence, severity, and risk factors of symptomatic treatment‐related pneumonitis in patients with lung cancer who received this sequential combination. Methods We conducted a retrospective study of a cohort of patients with lung cancer who received TRT after at least two cycles of PD‐(L)1 inhibitor treatment between January 2018 and August 2020. Treatment‐related pneumonitis was evaluated and analyzed to illustrate the safety profile of this sequential combination. Potential risk factors were explored by univariate and multivariate logistic regression analyses. Results Among the 828 patients with prior PD‐(L)1 inhibitor treatment, 96 patients receiving subsequent TRT were included in the analysis. Of these, 49 patients (51%) received radical TRT while 47 patients (49%) received palliative TRT. The median total dose was 52 Gy (IQR 50–60 Gy). The median time from the initiation of PD‐(L)1 inhibitor treatment to TRT was 4.8 months (1.6–14.1 months) with most of the patients (74%) administering no less than four cycles of PD‐(L)1 inhibitor. During follow‐up, 47 patients (48.96%) developed symptomatic treatment‐related pneumonitis (grade 2 n = 28, grade ≥3 n = 19) while six patients (6.25%) suffered from fatal toxicity. The median time of pneumonitis onset after completion of TRT was 35 days (0–177 days) with six patients developing during TRT. Pulmonary emphysema and lung V20 were demonstrated to be independent risk factors of symptomatic pneumonitis (OR: 5.67, 95% CI: 1.66–19.37, p = 0.006; OR: 3.49, 95% CI: 1.41–8.66, p = 0.007, respectively). Conclusion TRT after PD‐(L)1 inhibitor treatment resulted in significantly increased incidence and severity of treatment‐related pneumonitis in patients with lung cancer. Intensive attention should be emphasized to the safety of this sequential combination in clinical practice.